PENGEMBANGAN DAN PENINGKATAN KINERJA PAMONG BELAJAR SANGGAR KEGIATAN BELAJAR - Melati Indri Hapsari (JIV-Jurnal Ilmiah Visi, 2008)
The success of a Learning Activity Center much depends on the tutorsâ€™ competence and creativity. This articles discusses some variables influencing the tutorsâ€™ performance and puts forward a number of suggestions to improve the tutorsâ€™ performance.